Investigating the effects of organizational culture on brand promise - Hamed Abbasi; Hamid Reza Abbasi; Ashkan Faraji; Mahsan Hajirasouliha (Management Science Letters)
This paper studies the impacts of four components of organizational culture on brand promise in one of Iranian producer of detergent and sanitary products. The proposed study uses two questionnaires, one for measuring the effects of organizational culture and the other for brand promise in Likert scale. Cronbach alphas for organizational culture and brand promise are calculated as 0.83 and 0.91, respectively. The study has been implemented among 211 regular customers of producer of detergent and sanitary products. Using Spearman correlation ratio as well as stepwise regression analysis, the study has detected that three components of organizational culture including tribal culture, entrepreneurial culture, and market culture influence positively on brand promise and bureaucratic culture influences negatively on brand promise.